THE ARTISTIC AND PHILOSOPHICAL VALUE OF THE FEMALE THEME IN THE WORKS OF HEMINGWAY AND FAULKNER (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This paper explores the artistic and philosophical meaning of women’s portrayals in the literary works of Ernest Hemingway and William Faulkner. In Hemingway’s fiction, female figures represent ideals of freedom, love, and renewal, reflecting a search for identity and vitality in a changing world. In contrast, Faulkner’s women are portrayed within the confines of social pressure, moral conflict, and the disintegration of traditional values. The research demonstrates that these female characters function not merely as individual heroines but as symbolic embodiment of the moral, spiritual, and philosophical dimensions of their time.